GENDER MATTERS IN FINANCIAL INCLUSION, BUT WOMEN IN MANAGERIAL POSITIONS MAKE A DIFFERENCE. EVIDENCE FROM THE NAMIBIAN ENTERPRISES - Kamanzi, Adalbertus (International Journal of Gender Studies, 2022)
Purpose: The paper examines if gender matters in the financial inclusion in the enterprises of Namibia. Methodology: Using the Namibia Enterprise Survey Database (NESD) 2014/2015, which was collected from 580 enterprises by the World Bank, the paper tests a null hypothesis that there is no association between gender and financial inclusion in the Namibian enterprises. Findings: The article finds out that there is no difference between women's and men's top-managed enterprises in having a Cheque and saving accounts. It is also established that women have more access to mobile money facilities compared to men, on the one hand, and men have more accessibility to credit and loans compared to women, on the other hand. Such findings imply both an institutionalized gender financial inclusion divide and institutionalized financial inclusion equality between women and men's top-managed enterprises in Namibia. Hence, gender matters. Unique Contribution to Theory, Policy and Practice: The gender theory that women are victims in their conditions and positions with regard to men is not always applicable because women in positions of power are more strategic and have capacity and agency to influence processes. With preferential treatment to men, there is need for concerted efforts to invest in mobile money literacy and numeracy and the promotion of perceptions and attitudes that will lead to the use of mobile money technologies; with preferential treatment to women, there is need for policies to promote sharing of the risks of the cost of borrowing and also to promote entrepreneurship in the use of loans.